2010
DOI: 10.1007/s12262-010-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

6 Year Prospective Clinical Trial of Primary Repair Versus Diversion Colostomy in Colonic Injury Cases

Abstract: Management pathway of colonic injury has been evolving over last three decades. There has been general agreement that surgical methods dealing with colonic injury did not affect the outcome but there are certain independent risk factors for complications. These risk factors are still not clear and studies are going on to specify these risk factors. The primary objective of this study was to demonstrate that primary closure of colonic injury without colostomy in selective patient is safe. This was a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The colostomy is no longer the standard Treatment option due to its post-operative complications and the need for a subsequent operation (10). Even The colostomy itself is a cause of morbidity due to penetrating injuries to the colon (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The colostomy is no longer the standard Treatment option due to its post-operative complications and the need for a subsequent operation (10). Even The colostomy itself is a cause of morbidity due to penetrating injuries to the colon (12).…”
Section: Discussionmentioning
confidence: 99%
“…In cases with significant blood loss, dirt, and left side colon lesions, it was not recommended Lesions of more than two viscera in addition to colon lesions (16). However, recent research around the world has found that primary repair of traumatic colon injuries can be safely performed in almost all cases, including war injuries (10,12,17). In a study conducted in approximately 115 patients over a period of 2 decades who concluded that in patients without a planned anterior hernia (HPV), the primary anastomosis was a better treatment technique, with results showing around 0% complications compared to 36% of complications caused by colostomy (15) as it has the advantage of avoiding colostomy, postoperative care of the colostomy, and re-hospitalization and reoperation in terms of costs and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 19 ] However, the approach that colon injuries can be repaired without stoma, and the increase in expertise, have led to questioning of the treatment approach in rectal injuries, and in particular, to the view that all Ds should not be applied in all intraperitoneal rectal injuries. [ 20 22 ] It has finally come to both avoiding diverting stoma in appropriate cases but also withdrawing the routine use of distal washouts and presacral drainage, which increase intra-abdominal complications. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that primary repair or anastomosis was safe and effective; in fact, they reported fewer complications in the repair group as compared to those who underwent proximal diversion (Table 42.4). A further randomized study by Kamwendo [30] in 2002 confirmed the safety of primary repair. This study was important in that it included patients with delayed presentation, contamination, associated injuries, and shock.…”
Section: Evidence and Practice Guidelinesmentioning
confidence: 91%